Acidentes, envenenamentos e violências como causa de morte dos residentes no município de São Paulo, Brasil Accidents, poisonings and violences as causes of death in resident inhabitants of the city of S. Paulo, Brazil - Maria Helena Silveira; Sabina Lea Davidson Gotlieb (Universidade de São Paulo, 1976)
Foi estudado o comportamento das mortes violentas de residentes no município de São Paulo, nos anos 1970, 1971 e 1972. Essas causas, que representam, aproximadamente, 10% do total de óbitos ocorridos em cada ano, incluem todos os tipos de acidentes (trânsito, doméstico, do trabalho e outros), os suicídios, homicídios e todas as demais causas externas. Os tipos de morte foram analisados segundo sexo e grupo etário, sendo os resultados apresentados através de mortalidade proporcional e do risco de morrer por essas causas. The external causes of death for the residents of São Paulo, Brazil, are described according to mortality rates and ratios for the period 1970 to 1972. These causes of deaths (traffic, home and work accidents, homicides, suicides and all other) were responsible for 10% of the total deaths occurred in that period. The risk of death by external causes for all ages is 3,5 times higher for males (11,33‰ inhab.) than for females (3,09‰ inhab.). The death rate for motor vehicle accidents is increasing for both sexes in this period. The mortality rate for children less than one year old is very high and the main contribution was due to home accidents. Among the studied causes of death, homicide was a very important one for males aging 15 years old and over. The mortality ratio by suicide is higher for females than males but the risk of dying is higher for males.